2021
DOI: 10.1111/1467-9817.12345
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by which morphological awareness contributes to Chinese and English reading comprehension

Abstract: Background: Research has established the link between morphological awareness and reading comprehension. However, the theoretical mechanisms underlying the association remain unclear. This study examined the direct and indirect effects of morphological awareness on reading comprehension in L1 Chinese and L2 English, with a sample of Chinese children who speak English as a second language (ESL). We tested theoretically driven predictions regarding the ways in which morphological awareness might impact reading c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 38 publications
(79 reference statements)
1
26
1
Order By: Relevance
“…Second, morphological awareness facets had both direct and indirect effects on L2 reading comprehension through the mediation of lexical inference. Prior studies tested a few pathways assuming the developmental order of morphological awareness and vocabulary in L1 Chinese reading comprehension (Zhang, 2016a;Zhao et al, 2019;Kim et al, 2020;Qiao et al, 2021). Nevertheless, the current study found that morphological awareness and vocabulary knowledge were the two parallel components in predicting L2 Chinese reading comprehension.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Second, morphological awareness facets had both direct and indirect effects on L2 reading comprehension through the mediation of lexical inference. Prior studies tested a few pathways assuming the developmental order of morphological awareness and vocabulary in L1 Chinese reading comprehension (Zhang, 2016a;Zhao et al, 2019;Kim et al, 2020;Qiao et al, 2021). Nevertheless, the current study found that morphological awareness and vocabulary knowledge were the two parallel components in predicting L2 Chinese reading comprehension.…”
Section: Discussioncontrasting
confidence: 64%
“…The utility of morphological awareness has been endorsed in reading across languages. Several prior studies explored the facilitative role of morphological awareness in Chinese reading comprehension among the first language (L1) or bilingual children (Wang et al, 2006;Pan et al, 2016;Zhang, 2016a,b;Lin et al, 2018;Zhao et al, 2019;Qiao et al, 2021).…”
Section: Morphological Awareness In Chinese Reading Comprehension: Direct and Indirect Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, this special issue includes studies in Chinese (Cantonese; Qiao et al, 2021), French (Rassel et al, 2021), German (Fleischhauer et al, 2021;Görgen, De Simone, Schulte-Körne, & Moll, 2021) and Norwegian (Lyster et al, 2021) and studies in English that draw upon the varied educational contexts of the United Kingdom (Dawson et al, 2021;James et al, 2021), the United States (Goodwin et al, 2021) and Canada (Georgiou et al, 2021;Ginestet et al, 2021). Qiao et al (2021) explored the relationship between morphological awareness and reading comprehension in both Chinese and English with Chinese-English bilingual children in Hong Kong (8 to 10 years old). In both languages, morphological awareness contributed indirectly to reading comprehension through two paths: via word reading and via vocabulary to word reading.…”
Section: Cross-language Considerationsmentioning
confidence: 99%
“…Several papers in this special issue add to this body of evidence. For instance, the relationship between morphological awareness and reading ability is demonstrated cross-sectionally in French by Rassel, Facon, and Casalis (2021), in Chinese-English bilinguals by Qiao, Liu, and Yeung (2021) and longitudinally over a span of 9 years by Lyster, Lervag, Hulme, and Snowling (2021).…”
mentioning
confidence: 99%